Application of Savonius Type Turbine Technology for The Conversion of Low Speed Wind into Electrical Energy at Wong Polo Beach Kota Pari Village Indonesia - Parlin Siagian; Hamdani Hamdani; M. Erpandi Dalimunthe (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Utilization of the potential that exists in tourist attractions aims to increase the savings in expenses that must be borne by the community to manage tourism. The beach is a place that is rich and abundant in wind potential that can be used to drive wind turbines. To take advantage of the existing wind potential, of course, we must know how the wind potential is in the form of wind speed and locations that have wind speed potential and how to use it as energy to drive wind turbines. To obtain the potential of wind energy and utilize it, wind speed measurements are carried out using a digital anemometer and recorded for some time. The position of the measuring instrument installed must be protected from wind obstacles so that it is installed as high as 20 meters above the ground in an open position against the direction of the incoming wind. From the measurement results over a period of one day, the wind speed varies and changes at any time and the maximum value is 6 m/s during the day starting at 10:00 to 04:00. The wind speed profile obtained is analyzed and the type of turbine is determined according to the low wind speed below 10 m/s. From the analysis results, the appropriate turbine is the Savonius VAWT type and can produce electrical energy of approximately 2.43 Watts with a diameter of 0.11 m. The use of turbines for wind at low speeds will still have the potential to generate small-scale electrical energy for communities in coastal areas